Effects of exopeptidase treatment on antihypertensive activity and taste attributes of enzymatic whey protein hydrolysates. (March 2015) - Cheung, Lennie K.Y.; Aluko, Rotimi E.; Cliff, Margaret A.; Li-Chan, Eunice C.Y.
Highlights: ACE-inhibiting WPH was debittered using an aminopeptidase or a carboxypeptidase. Debittered WPH had ACE-inhibitory activity and antihypertensive activity in SHRs. The 200–1000 Da fractions had the highest ACE-inhibitory activity. Exopeptidase-treated WPHs had significantly lower bitterness and higher umami taste. Exopeptidase-catalyzed release of amino acids may explain the changes in taste. Abstract: The objectives of this study were to investigate the effects of exopeptidase treatment on ACE-inhibitory activity, antihypertensive activity and taste of whey protein hydrolysates (WPHs). WPH with high ACE-inhibitory activity (IC50  = 0.15 mg/mL) was treated with carboxypeptidase (Accelerzyme ® CPG), aminopeptidase (Peptidase R), or an aminopeptidase and proteinase mixture (ProteAX). The exopeptidase-treated hydrolysates exhibited ACE-inhibitory activity (IC50  = 0.24−0.34 mg/mL) and decreased systolic blood pressure (−12 to −31 mm Hg) in spontaneously hypertensive rats for 24 h after a single administration of 100 mg/kg body weight. The highest ACE-inhibitory activity was associated with the 200–1000 Da fractions in all exopeptidase-treated hydrolysates. Exopeptidase treatment significantly lowered bitterness, increased umami and salty tastes, and increased overall acceptability of the starting WPH, changes that may be due to release of certain terminal amino acids. Therefore, exopeptidase treatment may be a viable debittering method for bitter-tasting, antihypertensive protein hydrolysates, before incorporation into functional foods.